2008
DOI: 10.2754/avb200877020163
|View full text |Cite
|
Sign up to set email alerts
|

Blood Cell Morphology and Plasma Biochemistry of Captive Mauremys caspica (Gmelin, 1774) and Mauremys rivulata (Valenciennes, 1833)

Abstract: We found sex-dependent differences only in the Ca value in the blood biochemistry profile for healthy M. caspica. Sex-dependent differences were found only in albumin and P values in the blood biochemistry profile for healthy M. rivulata. No significant differences were found between males of both species in question with respect to plasma biochemistry values. However, only plasma total protein and Ca content levels differed significantly between the females of the two species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…We found heterophils and lymphocytes to be the most common cell types, with lymphocytes accounting for an average of 42% of the leukocyte population. The previous report is similar to other counts of captive turtles of various species (Metin et al, 2006;Metin et al, 2008), while our higher number is similar to what is found in most species of lizards, where heterophils and lymphocytes are the most common cell types (Fisse et al, 2004). It is unclear what could explain the different results, but many factors are known to alter leukocyte counts, including nutritional status, parasite load, and season (Fisse et al, 2004).…”
Section: The Journal Of Experimental Biology 216 (4)supporting
confidence: 89%
“…We found heterophils and lymphocytes to be the most common cell types, with lymphocytes accounting for an average of 42% of the leukocyte population. The previous report is similar to other counts of captive turtles of various species (Metin et al, 2006;Metin et al, 2008), while our higher number is similar to what is found in most species of lizards, where heterophils and lymphocytes are the most common cell types (Fisse et al, 2004). It is unclear what could explain the different results, but many factors are known to alter leukocyte counts, including nutritional status, parasite load, and season (Fisse et al, 2004).…”
Section: The Journal Of Experimental Biology 216 (4)supporting
confidence: 89%
“…Two diameters of erythrocytes were measured: erythrocyte length (EL) and erythrocyte width (EW). Nucleus length (NL) and nucleus width (NW) were measured using an Olympus ocular micrometer (Magnus MLM, Olympus India) at a magnification of 100×e, whereas erythrocyte and nucleus sizes (ES and NS) were calculated using the standard formulae: [(EL×EW×π)/4] and [(NL×NW×π)/4], respectively (Metin et al 2008).…”
Section: Morphology Of Blood Cellsmentioning
confidence: 99%
“…Haematological parameters are gaining increasing importance in aquaculture because of its value in assessing the health status of fish (Schütt et al, 1997;Kori-Siakpere et al, 2005;Metin et al, 2008;Karimi et al, 2013;Suely et al, 2016). Haematological parameters such as RBC, WBC, Hb, lymphocyte, and TPC are pivotal role in assessing the physiological condition of the fish.…”
Section: Blood Profilementioning
confidence: 99%